SYSTEMATIC LITERATURE REVIEW: MANAGEMENT AS A PHILOSOPHICAL AND SYSTEMATIC SCIENCE - Dahyar Husain; Usiono (RADJA PUBLIKA, 2024)
Management has developed into a complex and multidimensional scientific discipline, with a strong philosophical foundation and systematic methodology. However, the concept of management as a philosophical and systematic science is still not fully understood and explored in academic literature. This research aims to fill this gap by conducting a comprehensive systematic literature review (SLR) to analyze and synthesize studies relevant to this topic. Using a systematic and structured SLR method, this research identified and analyzed 67 studies that discussed philosophical and systematic aspects of management. The main findings are grouped into four themes: (1) philosophical foundations of management: values, ethics, and leadership; (2) systematic methodology in management: planning, organizing, directing and controlling; (3) integration of philosophical and systematic aspects in management practice; and (4) challenges and opportunities in implementing management as a philosophical and systematic science. This research contributes to the development of knowledge in the field of management by mapping and synthesizing relevant academic literature, as well as providing new insights for management academics and practitioners in integrating philosophical and systematic aspects in more effective and meaningful management practices. Limitations of the study and recommendations for future research are also discussed